Elevation to species level and redescription of Xysticus alpinus Kulczyński, 1887 stat. n. (Araneae, Thomisidae) - Ballarin, Francesco; Pantini, Paolo; Gobbi, Mauro (Zootaxa, 2018)
Xysticus alpinus Kulczyński, 1887 stat. n. from Central-Eastern Alps, previously considered a subspecies of X. lanio C. L. Koch, 1835, is analyzed in detail. Redescription of both sexes and illustrations of habitus and genitalia are provided. A careful comparison with the nominal species is carried out revealing clear differences in morphology and habitat preferences. In light of this evidence, its elevation to species level is proposed.